LAND SUITABILITY ASSESSMENT USING AHP (ANALYTICAL HIERARCHY PROCESS) AND SYS,1993 METHODS IN ARID AND SEMI-ARID REGIONS FOR RICE FARMING - R. J. Mohammed,; A. A. Suliman, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate the extent the land to productive due to the fact that climatic changes and the increase in population growth are reasons that led to an increase in the demand for food, especially in developing countries. Therefore, a scientific way must assess the suitability of lands for growing crops. This research aims to provide an integrated approach to the process of analyzing the suitability of agricultural lands for crop growth. Rice in the Al-Mishkhab region of Al-Najaf Governorate using the analytical hierarchy model AHP and compared with the method of (Sys, 1993) and the actual production in the field, 12 soil parameters were determined (electrical conductivity, soil interaction, cation exchange capacity, exchangeable sodium ratio, texture soil, lime, gypsum, organic carbon, drainage, soil depth, slope, flooding) and three criteria were added in the AHP method due to their importance in Iraqi soils, which are (total nitrogen, available phosphorus, crop class). The results were extracted and showed that all the results of the study Using the method (Sys, 1993) within the unsuitable range for cultivation N2, either using the analytical hierarchy method and giving varying importance to the above soil criteria, it was found that 12% Very suitable for S1, 60% suitable for agriculture S2, and 28% moderately suitable for S3. Identical to actual crop production in the study area.